EKSPLORASI TINGKAT EKOLITERASI DAN PRAKTIK PENGELOLAAN SAMPAH PESERTA DIDIK SEKOLAH DASAR - Hasna Khaerunnisa; Mohamad Setiadi, Pidi; Ramadhani Putri, Agnestasia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The issue of waste remains an environmental challenge, including in elementary schools, which play a strategic role in building ecological awareness from an early age. This study aims to explore ecoliteracy of fifth-grade elementary school students in relation to the implementation of IPAS learning and waste management practices in the school environment. The study uses a qualitative descriptive approach with fifth-grade class student as subjects. Data collection was conducted through interviews, observations, and documentation to obtain a factual description of IPAS learning, student behavior, and the school's waste management curricula. The results show that IPAS learning related to the environment is still dominated by conventional approaches with limited practical activities, resulting in relatively low student involvement. The ecoliteracy of students is at a basic level, characterized by an understanding of the environment that has not been fully internalized in their daily behavior, particularly in the practice of waste sorting. The school waste management system also does not optimally support the development of ecoliteracy due to limited facilities and the absence of sustainable management of organic waste, including that generated by the Makan Bergizi Gratis Program. These findings emphasize that strengthening eco-literacy requires the integration of practice-based IPAS learning, the cultivation of environmentally conscious behavior, and the support of a sustainable school system and culture.